Segurança ambiental e desenvolvimento sustentável: promoção da segurança humana em face de desastres ambientais (a partir do caso Mariana/MG) - Porto, Thiago Cirillo de Oliveira (2019)
The speech about unsafety and its outcome are present times’ signs, due to the unexpected, unmeasurable and unpredictable harms, which have been produced by either human beings or due to those ones produced by natural catastrophes that might have been hazardous to the ancestors: issues related to hunger, urban violence, unemployment, violent crimes, terrorism, sexual attacks, pollution, human rights’ violation. Thus being so, such harms display the lack of certainties, protection and safety as well, by excluding people from the contexts of society life. It is quite well known that adverse situations can occur to everyone – people and countries in different proportions whether being rich or poor. Nevertheless, today, safety is taken as nuclear in the panorama of worries for global society, mainly to protect people and the environment where they live in daily risk situations. Thence, the United Nations Development Program released, on its 1994’ annual report, the concept of Human Safety, which aims at the individuals’ protection as to economical safety, meal, sanitary, environmental, personal, community and political ones. On the other hand, for this study, the focus was to place the worry about Human Safety into the sphere of Environmental One, so that it makes sustainable development likely, as a challenge to the terrifying effects of an anthropic environmental disaster, specially, in relation to changes in the natural background, which are caused by such an action, taking, as the most recent illustration, the disaster in Mariana, Minas Gerais State, in 2015, with the overall objective to analyze the interrelationship between sustainable development and environmental security, in order to promote full human development, and specific objectives: addressing concepts about human security, specifically with regard to environmental safety; submit the dimensions of sustainable development; outline central aspects of the right to environment conducive to human development; talk about the environmental disaster in the city of Mariana/MG, so also contributing to future studies. The theme is broad field in questions under the new legislation, concluding that there are intrinsic and inseparable relationship between human security and human development, from the integrity of the environment and as such, must be present on the agendas of States, non-governmental organizations and society at large, in order to guarantee the rights and the dignity of all individuals. Because it is a new theme in its outlines the methodological basis of the study was theoretical, of qualitative nature, exploratory and descriptive, post, wrap bibliographic survey, allowing an overview about the phenomenon studied. In addition, the study aims to be a source of reflection and of interest to the community, contributing greatly to the whole society report on the obligation to have every subject of rights to repair the damage he caused economically to the legally protected from others regardless of law or agreement of wills and who has the ability to repair